Peningkatan Hasil Belajar Siswa Dengan Menggunakan Metode Diskusi Pada Mata Pelajaran Pai di SMAN 3 Padang - Retniati, Retniati (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
Based on the results obtained from the implementation of cycle I, it can be concluded that the group discussion method has succeeded in improving student learning outcomes in Islamic Religious Education subjects at SMAN 3 Lengayang. This increase is reflected in higher test scores after discussions, as well as increased student activity and participation in the learning process. However, some students still need further guidance to increase their confidence in discussions. Therefore, in the next cycle, efforts need to be made to facilitate students to be more active and confident in participating in group discussions.